A household-based survey of knowledge, attitudes and practices towards dengue fever among local urban communities in Taiz Governorate, Yemen. Issue 1 (December 2016) - Alyousefi, Thaker; Abdul-Ghani, Rashad; Mahdy, Mohammed; Al-Eryani, Samira; Al-Mekhlafi, Abdulsalam; Raja, Yahia; Shah, Shamusul; Beier, John
Abstract Background Yemen has witnessed several dengue fever outbreaks coincident with the social unrest and war in the country. The aim of the present study was to describe the knowledge, attitudes and practices (KAPs) of at-risk urban populations residing in Taiz, southwest of Yemen. In addition, factors possibly associated with poor preventive practices were investigated. Methods A household-based, cross-sectional survey was conducted in three urban districts encompassing 383 households. Data on the socio-demographic characteristics and KAPs of the participating household heads were collected using a pre-designed, structured questionnaire. The association of socio-demographic characteristics, knowledge and attitudes of the population with poor preventive practices against dengue fever was then analyzed using logistic regression. Results More than 90.0 % of respondent household heads had correct knowledge about fever, headache and joint pain as common signs and symptoms of dengue fever. Moreover, muscular pain and bleeding were perceived by more than 80.0 % of the respondents as being associated with dengue fever; however, only 65.0 % of the respondents reported skin rash as a sign of dengue fever. More than 95.0 % of respondents agreed about the seriousness and possible transmission of dengue fever; however, negative attitudes regarding the facts of being at risk of the disease and that the infection is preventable were expressed by 15.0 % of respondents. Despite the good level of knowledge and attitudes of the respondent population, poor preventive practices were common. Bivariate analysis identified poor knowledge of dengue signs and symptoms (OR = 2.1, 95 % CI = 1.24–3.68;P =  0.005) and its vector (OR = 2.1, 95 % CI = 1.14–3.84;P =  0.016) as factors significantly associated with poor preventive practices. However, multivariable analysis showed that poor knowledge of the vector is an independent predictor of poor preventive practices of the population (adjusted OR = 2.1, 95 % CI = 1.14–3.84;P  = 0.018). Conclusion The majority of people in urban communities of Taiz have a clear understanding of most signs/symptoms of dengue fever as well as positive attitudes towards the seriousness and possible transmissibility of dengue fever. However, negative attitudes regarding their perception of the risk and possible prevention of the infection are prevailing among a small proportion of the population and need to be targeted by educational campaigns. It appears that the good level of the population knowledge of the signs/symptoms of dengue fever and the factors contributing to the spread and control of its vectors did not translate into good practices.